1990
DOI: 10.1007/bf00315797
|View full text |Cite
|
Sign up to set email alerts
|

Auxin regulates the promoter of the root-inducing rolB gene of Agrobacterium rhizogenes in transgenic tobacco

Abstract: The regulation in tobacco of the rolB and rolC promoters of Agrobacterium rhizogenes pRi 1855 TL-DNA was studied by using the beta-glucuronidase (GUS) reporter system in transgenic plants. A 20- to 100-fold increase of GUS activity was selectively induced by auxin in rolB-GUS transformed mesophyll protoplasts, whereas this auxin-dependent increase was only 5-fold in rolC-GUS protoplasts. Moreover, both gene fusions exhibited similar tissue-specific expression in aerial parts but different patterns in roots. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
51
0
2

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 37 publications
6
51
0
2
Order By: Relevance
“…The expression of rolB in transgenic plants also has been extensively analyzed and found to be strongest in root and shoot meristems (Schmülling et al, 1989;Maurel et al, 1990;Altamura et al, 1991;Capone et al, 1991), which is in accord with an effect of the oncogene on meristem induction. Expression was also detectable in the vascular system.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The expression of rolB in transgenic plants also has been extensively analyzed and found to be strongest in root and shoot meristems (Schmülling et al, 1989;Maurel et al, 1990;Altamura et al, 1991;Capone et al, 1991), which is in accord with an effect of the oncogene on meristem induction. Expression was also detectable in the vascular system.…”
Section: Introductionmentioning
confidence: 89%
“…More recently, in cultured thin cell layers ( Tran Thanh Van et al, 1974), the stimulation of meristem formation has been shown to be the primary effect of rolB (Altamura et al, 1994). Expression of rolB greatly increases the sensitivity of transformed plant cells to auxin (Spanò et al, 1988;Maurel et al, 1991), and tyrosine phosphatase activity has been associated with the RolB protein when it is expressed in Escherichia coli (Filippini et al, 1996), suggesting that RolB may act by perturbing the auxin signal transduction pathway.The expression of rolB in transgenic plants also has been extensively analyzed and found to be strongest in root and shoot meristems (Schmülling et al, 1989;Maurel et al, 1990;Altamura et al, 1991;Capone et al, 1991), which is in accord with an effect of the oncogene on meristem induction. Expression was also detectable in the vascular system.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Coupling a promoter of such a gene to the coding sequence of an easily detectable marker gene such as gus would allow the establishment of a sensitive bioassay. et al (19) showed a 20-to 100-fold increase of GUS2 activity when mesophyll protoplasts of rolB-gus-transformed tobacco plants were incubated in auxin-containing culture medium. We have analyzed the hormonal response of a chimeric gene consisting of the Agrobacterium tumefaciens T-DNA gene 5 promoter (Pg5) fused to the gus coding sequence in mesophyll protoplasts of transgenic tobacco plants.…”
mentioning
confidence: 99%
“…The expression of several plant genes has been shown to be dependent on the presence of phytohormones (14,19,27). Coupling a promoter of such a gene to the coding sequence of an easily detectable marker gene such as gus would allow the establishment of a sensitive bioassay.…”
mentioning
confidence: 99%